Natural convection and entropy generation of hybrid nanofluid in double annulus separated by a thin rotating partition under magnetic field - Selimefendigil, Fatih; Chouikhi, Houssam; Öztop, Hakan Fehmi (Elsevier, 2023)
The present study analyzes the impacts of using a rotating partition on the natural convection and entropy generation of nanofluid filled double annulus under magnetic field by using finite volume method. Effects of various pertinent parameters such as Rayleigh number (Ra: 104 - 6 x 105), rotational Reynolds number (Rew: 0-100), Hartmann number (Ha: 0-60), fin height (Hf:0.1-0.5) and fin number (Nf:4-20) on the thermal performance improvements are numerically assessed. The contributions of rotations to the overall thermal performance become different depending upon the activation of rotations and magnetic field effects. Depending on whether rotations exist, magnetic field effects have different impact on the behavior of heat transport and entropy generation. Thermal performance reduction amounts become 40% without magnetic field when comparing the rotating and stationary interface cases. Fins further improve the thermal performance up to 23% depending upon the existence of magnetic field while rises with existence of magnetic field and increasing its strength for the case of non-rotating interface while it shows opposite behavior for rotating interface case. When the location of the interface becomes closer to the outer surface of the annulus, reduction of the entropy generation up to 68% can be obtained. Artificial neural network based model provides successful estimation of thermal performance and entropy generation when considering the impacts of rotating interface.
Keywords: Rotating partition; Nanofluid; Double annulus; Magnetic field; Finite volume method